Follicle Viability after Vitrification of Bovine Ovarian Tissue - Janaína de Souza Guedes; Jhenifer Kliemchen Rodrigues; Ana Luisa Menezes Campos; Camila Cruz de Moraes; João Pedro Junqueira Caetano; Ricardo Mello Marinho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose The present study aimed to evaluate the impact of vitrification on the viability of follicles using a three-dimensional (3D) in vitro culture. Methods Bovine ovarian tissue samples (n = 5) obtained from slaughterhouses were utilized. The cortex was cut into small fragments of 2 x 3 x 0.5 mm using a tissue slicer. From these fragments, secondary follicles were first isolated by mechanical and enzymatic methods, then encapsulated in alginate gel and individually cultured for 20 days. Additional fragments of the same ovarian tissue were vitrified in a solution containing 25% glycerol and 25% ethylene glycol. After warming, the follicles underwent the same follicular isolation process that was performed for the fresh follicles. Results A total of 61 follicles were isolated, 51 from fresh ovarian tissue, and 10 from vitrified tissue. After the culture, the vitrified and fresh follicles showed 20% and 43.1% survival rates respectively (p = 0.290),with no significant differences. At the end of the culture, therewere no significant differences in follicular diameter between the vitrified (422.93 ± 85.05 μm) and fresh (412.99 ± 102.55 μm) groups (p = 0.725). Fresh follicles showed higher mean rate of antrum formation when compared with vitrified follicles (47.1% and 20.0% respectively), but without significant difference (p = 0.167). Conclusions The follicles were able to develop, grow and form antrum in the 3D system after vitrification, despite the lower results obtained with the fresh tissue.